2011
DOI: 10.1371/journal.pone.0028323
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A/IFN-Gamma Triggers Autophagy-Related Necrotic Hepatocyte Death through IRGM1-Mediated Lysosomal Membrane Disruption

Abstract: Interferon-gamma (IFN-γ), a potent Th1 cytokine with multiple biological functions, can induce autophagy to enhance the clearance of the invading microorganism or cause cell death. We have reported that Concanavalin A (Con A) can cause autophagic cell death in hepatocytes and induce both T cell-dependent and -independent acute hepatitis in immunocompetent and immunodeficient mice, respectively. Although IFN-γ is known to enhance liver injury in Con A-induced hepatitis, its role in autophagy-related hepatocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…In WT fibroblasts, Irgm1 localized strongly to the surface of mitochondria in punctate concentrations (Fig. 7D), as reported previously by others (13). Similar to Irgm1 KO enterocytes, we found a much higher percentage of fused/tubular mitochondrial morphologies in Irgm1 KO fibroblasts (Fig.…”
Section: Irgm1 Deficiency Leads To Exaggerated Intestinal Inflammationsupporting
confidence: 90%
“…In WT fibroblasts, Irgm1 localized strongly to the surface of mitochondria in punctate concentrations (Fig. 7D), as reported previously by others (13). Similar to Irgm1 KO enterocytes, we found a much higher percentage of fused/tubular mitochondrial morphologies in Irgm1 KO fibroblasts (Fig.…”
Section: Irgm1 Deficiency Leads To Exaggerated Intestinal Inflammationsupporting
confidence: 90%
“…Two further rabbit polyclonal antibodies from Abcam plc (ab69464 and ab69465) were produced by immunisation with a peptide from the human homologue IRGM and were described as cross-reactive on mouse IRGM proteins (e.g. used to detect Irgm1 in (41)). We have now also produced two new reagents against the N-terminal peptide of the short isoform, MAETHYAPLSSAFPC (residues 17-31), in rabbit (rbMAE15) and in chicken (chMAE15).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous, interferon-induced mouse Irgm1 has been reported to be associated with mitochondria in RAW264.7 (30) and ML-1 4a hepatoma cells (41), using A19 and rabbit anti-human IRGM antisera respectively to detect Irgm1, and cardiolipin or O-N-nonyl acridine orange and Tom40 respectively as mitochondrial markers. A19 is a relatively weak reagent (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the mitochondrial membrane permeability is altered, and autophagy is activated, leading to lysosomal degradation of the affected mitochondria and caspase-independent cell death (80). Chang et al reported that IFN-γ, a potent Th1 cytokine, enhances autophagic flux and causes necrotic-type cell death in Con A-treated hepatocytes (81). The same group showed that the liver's blood vessels are the first target in both T cell-independent and T cell-dependent hepatitis.…”
Section: Autophagy and Susceptibility To Autoimmune Diseasesmentioning
confidence: 99%